Calcium and Calcineurin-NFAT Signaling Regulate Granulocyte-Monocyte Progenitor Cell Cycle via Flt3-L. (26th November 2014) - Fric, Jan; Lim, Clarice X.F.; Mertes, Alexandra; Lee, Bernett T.K.; Viganò, Elena; Chen, Jinmiao; Zolezzi, Francesca; Poidinger, Michael; Larbi, Anis; Strobl, Herbert; Zelante, Teresa; Ricciardi-Castagnoli, Paola
Abstract : Maintenance of myeloid progenitor cells is controlled by complex regulatory mechanisms and is orchestrated by multiple different transcription factors. Here, we report that the activation of the transcription factor nuclear factor of activated T cells (NFAT) by calcium-sensing protein calcineurin inhibits the proliferation of myeloid granulocyte–monocyte progenitors (GMPs). Myeloid progenitor subtypes exhibit variable sensitivity to induced Ca 2+ entry and consequently display differential engagement of the calcineurin-NFAT pathway. This study shows that inhibition of the calcineurin-NFAT pathway enhances the proliferation of GMPs both in vitro and in vivo and demonstrates that calcineurin-NFAT signaling in GMPs is initiated by Flt3-L. Inhibition of the calcineurin-NFAT pathway modified expression of the cell cycle regulation genes Cdk4, Cdk6, and Cdkn1a ( p21 ), thus enabling rapid cell cycle progression specifically in GMPs. NFAT inhibitor drugs are extensively used in the clinic to restrict the pathological activation of lymphoid cells, and our data reveal for the first time that these therapies also exert potent effects on maintenance of the myeloid cell compartment through specific regulation of GMP proliferation. Stem Cells 2014;32:3232–3244